The Effect of Educational Video About Maternal Health Related to COVID-19 to Knowledge Level of Medical Student - Aulika Alya Paramesti; Putri Sekar Wiyati; Diah Rahayu Wulandari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background : There have not been many cases of COVID-19 infection in pregnant women before, during and after gavebirth, so knowledge about COVID-19 infection in pregnancy and the fetus is still limited. This research is expected to provide basic data for further studies and provide new knowledge, especially regarding maternal health related to COVID-19, considering that currently COVID-19 is a new type of virus and is currently a pandemic.Objectives : This study aimed to to determine the effect of educational videos about maternal health related to COVID-19 on the level of knowledge of Medical Students.Methods : This research was a pre-experimental research design design using the form of a